Desain Sistem Kendali Listrik Jarak Jauh Berbasis Internet of Things: Design of Remote Electricity Control System Based on Internet of Things - Franky Manoppo; Andreas Sumendap; Rosdiana Simbolon; Tony Laloan; Gede Erik Aktama; Riyando Assire Siregar; Muhamad Dwisnanto Putro (Jurnal Teknik Informatika, 2023)
Abstract — Designing a remote control can enable users without directly visiting the system. Controlling the source of electricity impacts increasing the efficiency of a system's performance and leads to monitoring and analyzing savings. Internet of Things network design is proposed in this research to control electrical equipment from an electrical panel source. The connection system between the Wemos D1 microcontroller and the designed Website can turn on and off the power lines on different building floors through a website information system. This study also describes the working system of data transmission between the Wemos D1 microcontroller and the Website by proposing a two-position control system design, namely on/off, based on the method of Observation, Interview, and Literature study. This study offers a prototype with C programming language as a Wemos D1 microcontroller design and information system simulation with HTML, CSS, Javascript, Node.js, and MongoDB as a Website design. The result is a two-position control system prototype that can operate properly to turn on and off the power lines on the 3rd and 4th floors, thereby increasing efficiency in terms of time and energy. Key words— Control System, Internet of Things, Two Positions, Wemos D1, Website   Abstrak — Perancangan sebuah kendali jarak jauh dapat memudahkan penggunanya tanpa mengunjungi secara langsung sistem tersebut. Pengendalian sumber listrik berdampak untuk peningkatan efesiensi kinerja sebuah sistem serta bermuara pada sebuah monitoring dan analisa penghematan. Sebuah desain jaringan internet of things diusulkan pada penelitian ini untuk mengendalikan peralatan listrik dari sebuah sumber panel listrik. Sistem koneksi antara mikrokontroler Wemos D1 dan Website yang dirancang dapat menghidupkan dan mematikan jalur listrik pada lantai bangunan yang berbeda melalui sebuah sistem informasi website. Studi ini juga memamparkan sistem kerja transmisi data antara mikrokontroler Wemos D1 dan Website dengan mengusulkan sebuah perancangan sistem kontrol dua posisi yaitu on/off berdasarkan metode Observasi, Wawancara and Studi pustaka. Studi ini menawarkan sebuah prototipe dengan bahasa pemrograman C sebagai perancangan mikrokontroler Wemos D1 dan simulasi system informasi dengan HTML, CSS, Javascript, Node.js, MongoDB sebagai perancangan pada Website. Hasilnya adalah sebuah prototipe sistem kontrol dua posisi yang dapat beroperasi dengan baik untuk menghidupkan dan mematikan jalur listrik di lantai 3 dan 4, dengan demikian dapat meningkatkan efisiensi dalam hal waktu dan juga tenaga. Kata kunci — Sistem Kontrol, Internet of Things, Dua Posisi, Wemos D1, Website.